Controllable heteroatom doping effects of CrxCo2-xP Nanoparticles: A Robust Electrocatalyst for Overall Water Splitting in Alkaline Solutions. - Wu,J; Li,P; Parra-Puerto,A; Wu,S; Lin,X; Kramer,D; Chen,S; Kucernak,ARJ (ACS Applied Materials and Interfaces, 2020)
The effect of doping Cr on the electrocatalytic activity of supported Co2P for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline solution was investigated. A beneficial improvement in the performance of Co2P supported on carbon black (CrxCo2-xP/CB) towards HER and OER was discovered. For the HER at -200 mV overpotential the turnover frequency (TOF) increases almost six-fold from 0.26 to 1.52 electrons siteCo-1 s-1 when Co2P/CB has a small amount of Cr added to form Cr0.2Co1.8P/CB. Similarly, we estimate an increase from 0.205 to 0.585 electrons siteCo-1 s-1 for the OER at 1.6V for the same change in composition. With 10at% Cr doping, the Cr0.2Co1.8P/CB catalyst needed 226 mV overpotential to produce a cathodic current density of -100 A g_Co^(-1) and 380 mV overpotential to produce an anodic current density of 100 A g_Co^(-1). Based on both experimental results and theoretical calculations, the activity improvement results from optimization of electronic properties of Co2P after Cr doping.